Performance analysis of multi-hop routing protocols in SDN-based wireless networks. (January 2022) - Ashtari, Sepehr; Abdollahi, Mahrokh; Abolhasan, Mehran; Shariati, Negin; Lipman, Justin
Abstract: Wireless cellular networks have rapidly evolved to be software-defined in nature. This has created opportunities to improve their performance. One such opportunity is through enabling programming and integration of multi-hop device-to-device (MD2D) at the edge. However, efficient integration of MD2D at the edge requires a highly adaptable and scalable routing protocol, where its development is underpinned through understanding of which type of current routing characteristics and architectures are suitable over dynamic networking conditions. To develop such understanding, we conducted a detailed analysis and performance study on three routing protocols, namely virtual ad-hoc routing protocol-source based (VARP-S) Abolhasan et al. (2018), SDN-based multi-hop device-to-device routing protocol (SMDRP) Abdollahi et al. (2019) and hybrid SDN architecture for wireless distributed networks (HSAW) Abolhasan et al. (2015). Our investigations illustrate that VARP-S and SMDRP perform best in terms of energy consumption and cellular routing overhead. However, HSAW shows better performance in terms of end-to-end (E2E) delay and packet loss over lower network and traffic densities. Graphical abstract: Highlights: A detailed performance analysis of three SDN-based routing protocols for 5G network. A system model compatible with 5G networks is designed. Comparison of the routing protocols in distinct network environments.